The Role of Digital Metacognitive Prompts Assisted by Gen-AI and Ethnopedagogical Approaches to Improve Writing Skills - Apriyadi, Hendra; Suryoputro, Gunawan; Tarmini, Wini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Developing students' writing skills, particularly in the context of 21st-century education, demands critical, reflective, and creative thinking. Practical writing skills depend not only on technical language skills but also require metacognitive awareness. However, many students still struggle to develop structured and reflective writing strategies. On the other hand, advances in artificial intelligence technology, particularly Generative AI (Gen-AI), provide significant opportunities to create adaptive and personalized digital learning environments, including providing metacognitive prompts that can stimulate students' deeper thinking awareness. This study aimed to explore the impact of Gen-AI-assisted digital metacognitive prompts and an ethnopedagogical approach to collaborative and individual learning processes on writing skills and metacognitive awareness. This study used a quasi-experimental approach with 200 high school students. Data analysis included MANOVA, two-way ANOVA, and multiple regression to investigate the impact of the intervention on the four groups. The research findings indicate that integrating Gen-AI-assisted digital metacognitive prompts and an ethnopedagogical approach in collaborative writing significantly improved metacognitive knowledge and regulation compared to other intervention groups. The implications of this study suggest that integrating Gen-AI-assisted digital metacognitive prompts and an ethnopedagogical approach can be an effective learning strategy in improving students' writing skills.